Between global aspiration and local reality: English Teaching in Indonesian primary schools: Prospects, barriers, and policy innovations - Marzul Hidayat; Fortunasari Fortunasari; Ella Masita (Jurnal Sinar Edukasi, 2025)
This paper explores the philosophical and practical tensions shaping English Language Teaching (ELT) in Indonesian primary schools, focusing on the interplay between global educational demands and local pedagogical realities. Situated within language policy studies and critical pedagogy, it examines how Indonesia’s pursuit of global competitiveness through early English instruction intersects with its multicultural, multilingual, and geographically diverse education system. The study highlights potential benefits of early English learning, including cognitive development, enhanced economic mobility through linguistic capital, and alignment with ASEAN regional integration goals. Yet, it also interrogates persistent barriers such as the shortage of qualified English teachers for young learners, stark urban-rural disparities in resources, and the epistemological clash between standardized global frameworks and Indonesia’s linguistic diversity. Analyzing recent policy reforms—particularly the Kurikulum Merdeka and its decentralization principles—the paper illustrates how educational innovations seek to balance universalist language paradigms with culturally grounded approaches. Employing critical discourse analysis, statistical review, and philosophical reflection, the study argues that sustainable ELT must transcend the global-local binary, embracing integrative pedagogies that respect Indonesia’s cultural and linguistic richness while fostering global engagement. Ultimately, the paper recommends context-responsive teacher development, culturally relevant curriculum design, and equitable policy implementation to reimagine English education as a space for both global participation and the affirmation of local identity.